MAGNESIAN GRANITOIDS (SANUKITOIDS) OF THE KOSTOMUKSHA AREA, WESTERN KARELIA: PETROLOGY, GEOCHRONOLOGY, AND TECTONIC ENVIRONMENT OF FORMATION - Samsonov A.V.; Larionova Yu.O.; Bibikova E.V.; Petrova A.Yu.; Puchtel I.S. (My University, 2004)
Geological-structural, petrochemical, isotopic and geochronologic data on late-tectonic granitoid massifs and dikes cutting the metavolcanics of the Kostomuksha greenstone belt, western Karelia were discussed. The intrusions were emplaced at 2715 ± 5 Ma into deformed metavolcanic sequences and were later subjected to structural-tectonic reworking together with their host rocks. The granitoids showed the same variations in the contents of major, trace and rare-earth elements. It was found that the contents of Zr and rare alkalis increase in the diorites and decrease in the granodiorites.